1994
DOI: 10.1095/biolreprod50.3.553
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical Localization of Vasoactive Intestinal Peptide and Neuropeptide Y in the Bovine Ovary

Abstract: The distribution of the neuropeptides vasoactive intestinal peptide (VIP) and neuropeptide Y (NPY) was studied immunocytochemically in bovine ovaries from 3 mo of gestation up to and including puberty, and from adult cows at three stages of the estrous cycle. The appearance of VIP and NPY immunoreactivity of 4.5-6 mo of gestation coincided with the onset of follicular development. In contrast to NPY, VIP was first found in the cortex. Both VIP and NPY immunoreactivity increased with age. From 9 mo of gestation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 36 publications
2
23
3
Order By: Relevance
“…Evidence exists to document the presence of VIP mRNA in the rat ovary (Gozes & Tsafriri 1986). Later studies with bovine ovaries suggest granulosa cells as also a probable site of biosynthesis of VIP (Hulshof et al 1994).…”
Section: Changes In Ovarian Vipmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence exists to document the presence of VIP mRNA in the rat ovary (Gozes & Tsafriri 1986). Later studies with bovine ovaries suggest granulosa cells as also a probable site of biosynthesis of VIP (Hulshof et al 1994).…”
Section: Changes In Ovarian Vipmentioning
confidence: 99%
“…A possibility to consider is that at least a fraction of the VIP regulation of estradiol release involves changes in locally produced VIP (Gozes & Tsafriri 1986, Hulshof et al 1994. From a regulatory perspective, it is difficult to compare levels of VIP used (10-6 M; w3700 ng/ml) in the in vitro studies with ovarian tissue levels of VIP (w150 pg/ovary).…”
Section: Changes In Ovarian Vipmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the phase dependent changes in blood pressure after administration of NPY into the vessels pre-treated with α 1 -, and α 2 -adrenergic receptors agonists and α 1 -, and α 2 -adrenergic receptors antagonists were observed. It has been shown, that NPY is co-localized with NE in nerve fibres supplying blood vessels of the reproductive tract and that it affects the contractile activity of these vessels, in part via its own receptors and in part by the synergistic action with NE (Hulshof et al, 1994;Majewski et al, 1995). The studies of (Dynarowicz et al, 1988) have revealed that ovarian steroids affect the reactivity of adrenergic and cholinergic receptors in the porcine ovarian and uterine arteries as well as they change the process of release, intake and elimination of NE.…”
Section: Original Papermentioning
confidence: 99%
“…The presence of numerous NPY-IR nerve fibres around blood vessels in the reproductive tract suggests that NPY participates in the regulation of blood flow through these organs (Hulshof et al, 1994;D'Albora et al, 2000). NPY is localised alone, or it is co-localised with norepinephrine (NE) in nerve fibres supplying blood vessels of the reproductive tract.…”
mentioning
confidence: 99%